Digital agriculture tools have reached 24% of rice and maize producers (around 4,000 ha), increasing 2020 yields by 26% on average (41% maize, 12% rice) in Colombia - CGIAR Research Program on Rice (2021)
In 2013, the Alliance of Bioversity-CIAT and Fedearroz, Fenalce, and the Ministry of Agricultural and Rural Development initiated a technical and scientific cooperation agreement to increase the federations’ capacity to model and analyze climatic information to identify potential agricultural threats and develop management options. Since then, every year, the federations have used diverse strategies to improve rice and maize production in Colombia, mainly through farmers’ workshops where agroclimatic knowledge is disseminated to influence farmers’ management decisions.